Machine Learning-Driven Analysis of Low-Carbon Technology Trade and Its Economic Impact in the USA - Gazi, Md Sumon; Barua, Ayan; Karim, Fazle; Siddiqui, Md Ismail Hossain; Das, Niropam; Islam, Md Raisul; Zeeshan, MD Abdul Fahim; Rahman, Md Anisur; Al Montaser, Md Abdullah (Journal of Ecohumanism, 2025)
The transition to sustainable energy is paramount for addressing climate change, and low-carbon technologies play a pivotal role in this shift in the USA. The prime objective of this research paper was to apply the capabilities of machine learning in an examination of America’s low-carbon technology trading. With powerful analysis tools, we attempted to detect trends in exporting and importing, estimate the contribution of such technology to the economy, and estimate the effectiveness of supporting policies. The scope of our activity was U.S. low-carbon technology trade, both its imports and its exports. Examining a rich dataset including volumes of trade, technological categories, and economic factors, we try to unveil deeper trends driving this new sector. The dataset for analysis in such a case involved in-depth information drawn from a range of reliable sources, including U.S. trade reports, economic statistics, and global databases for sustainability. Trade volumes, in terms of value and quantity of low-carbon technology exported and imported, form one of the key variables in such a dataset. There was extensive information about carbon emissions, providing an analysis of the impact on terms of the environment through such technology, and policy incentives, in terms of government actions for encouragement of low-carbon alternatives. In selecting machine learning models for examining low-carbon technology trade, three candidates—Logistic Regression, Support Vector Machines (SVM), and K-Nearest Neighbor (KNN)—stood out for their particular strengths. In terms of accuracy, the SVM model is the top scorer, closely followed by KNN, while Logistic Regression takes a considerable drop, indicating its relatively lower predictive capability. Precision measurements also rank similarly, with SVM and KNN recording high precision values, suggesting that they are reliable in predicting true positives. Recall scores also indicate the strength of SVM and KNN in recalling all instances, while the Logistic Regression model records lower recall, particularly in predicting the class. Finally, the F1 score, being the trade-off between precision and recall, further reinforces the superior performance of SVM and KNN, as both models record high scores, with Logistic Regression lagging. To enhance the U.S. position in the global low-carbon technology market, a multi-faceted approach must be taken. Firstly, efforts must be made to drive innovation through increased investment in research and development (R&D). For business firms and investors, the transition to a low-carbon economy presents a plethora of market opportunities in the low-carbon technology sector. U.S. firms can leverage growing consumer demand for green products by developing product lines to cater to renewable energy systems, energy-efficient appliances, and electric vehicles. For investors, an understanding of the dynamics of the low-carbon technology market is essential for risk management through predictive economic modeling. It is necessary to synchronize trade policy with U.S. and global carbon reduction objectives to foster a sustainable economy.